A Large-Scale Study on the Preferred Learning Mode in Higher Education: Which One Suits Me Better in the New Normal? - Affouneh, Saida; Salha, Soheil; Agyemang Adarkwah, Michael; Tlili, Ahmed (International Journal of Emerging Technologies in Learning (iJET), 2024)
With the end of school closures due to COVID-19, students had to return to school, where they were exposed to various learning pedagogies while adhering to health restrictions. In this era known as the “new normal,” several organizations, such as UNESCO, have urged the investigation of effective learning strategies and methods to ensure positive learning outcomes. This study aims to investigate students’ preferred learning mode in the new normal. A sequential mixed-methods approach was conducted with 3139 university students. The results revealed that students were divided about their preferred learning mode in the new normal. More than half of them believed that blended and online learning were the future of education, while the rest believed that face-to-face learning was more appropriate.